2008
DOI: 10.1111/j.1365-2435.2008.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Tails of enticement: caudal luring by an ambush‐foraging snake (Acanthophis praelongus, Elapidae)

Abstract: Summary 1.Ambush foragers that attract prey via luring provide an opportunity to examine how a predator's behaviour influences its dietary composition. 2. Australian death adders ( Acanthophis praelongus , Elapidae) are heavy-bodied ambush foragers with broad diets; the snake's modified tail-tip is waved to attract prey. Female adders have shorter tails than males, but longer terminal spines. 3. We videotaped captive snakes interacting with potential prey items (lizards and frogs) to document which prey types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…For example, a predator may wait to ambush prey with a lure out, a typical fishing strategy (e.g. [34]). This ability comes with a well-justified tradeoff [35] as the behaviour requires either a large brain or an investment in physical structures or substances to attract prey.…”
Section: Model and Resultsmentioning
confidence: 99%
“…For example, a predator may wait to ambush prey with a lure out, a typical fishing strategy (e.g. [34]). This ability comes with a well-justified tradeoff [35] as the behaviour requires either a large brain or an investment in physical structures or substances to attract prey.…”
Section: Model and Resultsmentioning
confidence: 99%
“…The detailed studies on A. praelongus have supported several hypotheses about the biology of death adders: for example, they have shown that the caudal lure is effective at attracting some but not all potential prey, with vulnerability greater for some prey taxa [14] and some body sizes [32]. Hence, reliance on this tactic may influence dietary composition [10].…”
Section: Discussionmentioning
confidence: 99%
“…The 'tendency to attack toads' is a complex trait in death adders and involves caudal luring of potential prey, as well as visual and olfactory assessment before launching a strike. Death adders are more likely to caudal lure in response to cane toads than to native anurans (Hagman et al, 2008(Hagman et al, , 2009). Thus, variation in the tendency to caudal lure in response to toads may underlie much of the variation in a snake's tendency to attack this novel type of prey.…”
Section: Discussionmentioning
confidence: 99%
“…The floodplain death adder Acanthophis praelongus is a dangerously venomous, ambush-foraging snake native to tropical Australia (Cogger, 2000). Floodplain death adders are highly susceptible to toad toxin (Phillips, Brown & Shine, 2003), consume frogs as a natural part of their diet (Webb, Shine & Christian, 2005; and use caudal luring to attract prey (Hagman, Phillips & Shine, 2008). This combination of traits renders this floodplain adder highly susceptible to impact from toads (Hagman, Phillips & Shine, 2009).…”
Section: Introductionmentioning
confidence: 99%